The N6‐methyladenosine modification enhances ferroptosis resistance through inhibiting SLC7A11 mRNA deadenylation in hepatoblastoma. Issue 5 (6th May 2022) - Liu, Li; He, Jiangtu; Sun, Guifeng; Huang, Nan; Bian, Zhixuan; Xu, Chang; Zhang, Yue; Cui, Zhongqi; Xu, Wenqiang; Sun, Fenyong; Zhuang, Chengle; Man, Qiuhong; et al.
Abstract: Background: Solute carrier family 7 member 11 (SLC7A11) is overexpressed in multiple human tumours and functions as a transporter importing cystine for glutathione biosynthesis. It promotes tumour development in part by suppressing ferroptosis, a newly identified form of cell death that plays a pivotal role in the suppression of tumorigenesis. However, the role and underlying mechanisms of SLC7A11‐mediated ferroptosis in hepatoblastoma (HB) remain largely unknown. Methods: Reverse transcription quantitative real‐time PCR (RT‐qPCR) and western blotting were used to measure SLC7A11 levels. Cell proliferation, colony formation, lipid reactive oxygen species (ROS), MDA concentration, 4‐HNE, GSH/GSSG ratio and cell death assays as well as subcutaneous xenograft experiments were used to elucidate the effects of SLC7A11 in HB cell proliferation and ferroptosis. Furthermore, MeRIP‐qPCR, dual luciferase reporter, RNA pulldown, RNA immunoprecipitation (RIP) and RACE‐PAT assays were performed to elucidate the underlying mechanism through which SLC7A11 was regulated by the m6A modification in HB. Results: SLC7A11 expression was highly upregulated in HB. SLC7A11 upregulation promoted HB cell proliferation in vitro and in vivo, inhibiting HB cell ferroptosis. Mechanistically, SLC7A11 mRNA exhibited abnormal METTL3‐mediated m6A modification, which enhanced its stability and expression. IGF2 mRNA‐binding protein 1 (IGF2BP1) was identified as the m6A reader of SLC7A11, enhancing SLC7A11 mRNA stability and expression by inhibiting SLC7A11 mRNA deadenylation in an m6A‐dependent manner. Moreover, IGF2BP1 was found to block BTG2/CCR4‐NOT complex recruitment via competitively binding to PABPC1, thereby suppressing SLC7A11 mRNA deadenylation. Conclusions: Our findings demonstrated that the METTL3‐mediated SLC7A11 m6A modification enhances HB ferroptosis resistance. The METTL3/IGF2BP1/m6A modification promotes SLC7A11 mRNA stability and upregulates its expression by inhibiting the deadenylation process. Our study highlights a critical role of the m6A modification in SLC7A11‐mediated ferroptosis, providing a potential strategy for HB therapy through blockade of the m6A‐SLC7A11 axis. Abstract : Upregulation of SLC7A11 promotes hepatoblastoma tumorigenesis by enhancing ferroptosis resistance. METTL3/IGF2BP1/m6A modification enhances the SLC7A11 mRNA stability and expression via inhibiting the deadenylation in an m6A‐dependent manner. The competitive binding of IGF2BP1 blocks PABPC1 from recruiting the BTG2/CCR4‐NOT complex, thereby suppressing the deadenylation of SLC7A11 mRNA.